The Imd pathway is involved in antiviral immune responses in Drosophila. - Costa, A.; Jan, E.; Sarnow, P.; Schneider, D. (PLoS ONE, 2009)
Cricket Paralysis virus (CrPV) is a member of the Dicistroviridae family of RNA viruses, which infect a broad range of insect hosts, including the fruit fly Drosophila melanogaster. Drosophila has emerged as an effective system for studying innate immunity because of its powerful genetic techniques and the high degree of gene and pathway conservation. Intra-abdominal injection of CrPV into adult flies causes a lethal infection that provides a robust assay for the identification of mutants with altered sensitivity to viral infection. To gain insight into the interactions between viruses and the innate immune system, we injected wild type flies with CrPV and observed that antimicrobial peptides (AMPs) were not induced and hemocytes were depleted in the course of infection. To investigate the contribution of conserved immune signaling pathways to antiviral innate immune responses, CrPV was injected into isogenic mutants of the Immune Deficiency (Imd) pathway, which resembles the mammalian Tumor Necrosis Factor Receptor (TNFR) pathway. Loss-of-function mutations in several Imd pathway genes displayed increased sensitivity to CrPV infection and higher CrPV loads. Our data show that antiviral innate immune responses in flies infected with CrPV depend upon hemocytes and signaling through the Imd pathway.